Screening for pesticides (to develop a scheme for testing) - Ismail, Roseny Augustina (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2004)
Pesticide poisoning is an important cause of morbidity and mortality in many countries in the world. Pesticides are substances or mixture of substances for controlling pest. Because of its hazardous property for killing the pests, pesticides are also always harmful for human beings if there are not used wisely and carefully. There are still many types of pesticides that are available in the market although many types of them had been banned to be produced or to be sold. For the purpose of pesticide screening, classification of pesticides is based on their chemical properties. This project focuses on pesticides which are classified as organochlorine hydrocarbons, chlorinated phenoxy acids, organophosphorus pesticides, carbamate pesticides and paraquat. In this project, pesticides from each class were added to an artificial biological sample of stomach content. Then, the pesticides in the stomach contents are extracted with various types of solvents and mixture of solvents. In each step, the adjustment of pH is so important because the solubility of pesticides in solvents may be depending on the pH of the sample. By following this method of extraction, at the end of the project the best solvent and the suitable pH for extracting pesticides in biological samples will be known. After extracting the stomach contents, all fractions of the organic layer that are collected in each extraction step, will be evaporated and the residue will be subjected to thin layer chromatography (TLC) for identification of pesticides. Beside identification of pesticides by using TLC, identification of paraquat will be made separately and estimated quantitatively. Chromatograms of TLC of different pesticides will be developed using different solvent systems according to their chemical nature. The suitability of spray reagent to a particular class of compounds is also a main concern in this project. This is to confirm the presence of pesticides in extracted solvents. The Rt value of the samples and Rt value of the standards will be compared and pesticides that have extracted will be identified. The presence of pesticides in a particular solvent will indicate that the pesticides are soluble in that solvent. Then, the solvent that extracted most of the pesticides will be concluded as the best solvent to use for extraction. At the end of this project, a simple scheme of extraction will be developed and this scheme can be used for screening pesticides in pesticide poisoning cases especially when the pesticide is unknown. The scheme is useful for the usage of laboratories which lack of modern automated instrument for screening pesticides.